The Influence of Digital Marketing and Product Innovation Product Innovation on Competitive Advantage And its Implications on Performance Marketing (A Survey of Smes Assisted by The Department of Trade and Industry of Bandung City) - Astri Kusendang; Agus Mulyana; Feby Febrian (Greenation International Journal of Law and Social Sciences, 2023)
The purpose of this research was to determine and analyze digital marketing, product innovation, competitive advantage and marketing performance, the effect of digital marketing and product innovation simultaneously and partially on competitive advantage, and the effect of competitive advantage on marketing performance in SMEs/IKM assisted by the Department of Trade and Industry. Bandung. The population in this research were SMEs/IKM assisted by the Department of Trade and Industry of Bandung City. The research method used in this research was descriptive survey method with a sample of 80 respondents, and the data analysis method used was path analysis using SPSS version 23 data processing software. Based on the result of the research found that the digital marketing, product innovation, competitive advantage and marketing performance in SMEs/IKM assisted by the Department of Trade and Industry of Bandung City has a category that wasalready high. Digital marketing and product innovation simultaneously have a positive effect on competitive advantage with a coefficient of determination of 40.9%, partially digital marketing variables was the most dominant variable affecting the competitive advantage. Competitive advantage has a positive and significant effect on marketing performance with a determination coefficient of 80.8%. Another important finding from this research is that digital marketing and product innovation indirectly have a positive effect on marketing performance through the competitive advantage variable.